2000
DOI: 10.1007/s005350070024
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis caused by amebiasis

Abstract: We report a case of appendicitis caused by amebiasis in a 45-year-old Japanese man. He presented to our hospital with bloody stools in June 1998. Sigmoidoscopy disclosed erosion, and a biopsy of the erosion showed colitis caused by Entamoeba histolytica infection. Four months later, he was admitted to our hospital with a small elastic mass and severe pain in the lower quadrant of the abdomen, which was diagnosed as acute appendicitis. He underwent appendectomy. Histopathological examination revealed numerous E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Appendicitis related to E. histolytica presence is quite rare and generally involve in literature as case reports (18,(31)(32)(33)(34)(35). Exact incidence of this atypical presentation of parasitic disease is not well known (36).…”
Section: E Vermicularis Is the Most Prevalent Helminthic Infectious mentioning
confidence: 99%
“…Appendicitis related to E. histolytica presence is quite rare and generally involve in literature as case reports (18,(31)(32)(33)(34)(35). Exact incidence of this atypical presentation of parasitic disease is not well known (36).…”
Section: E Vermicularis Is the Most Prevalent Helminthic Infectious mentioning
confidence: 99%
“…Yersinia enterocolitica has been isolated in 3–9% of inflamed appendices (43,44). Enterobius vermicularis has been identified in 2.5–4% of the appendectomies (45,46), and cases of appendicitis caused by amebiasis (47) and actinomycosis (48) have been reported. Searching for Helicobacter pylori in the appendix showed that it does not colonize the appendix and is unlikely to be a pathogenic stimulus for appendicitis (49).…”
Section: Pathogenesis Of Acute Appendicitismentioning
confidence: 99%
“…Amoebiasis has been the cause of death in elderly at general hospital of Mexico in 60 century (4). E.histolytica caused intestinal infection, but extra intestinal amoebiasis such as liver abscess, thoracic, genital amoebiasis, acute appendicitis and brain abscess have also been reported (2,(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%